School-Based Incentives and Teachers’ Commitment to Classroom Instruction in Public Secondary Schools: Evidence from Kwimba District, Tanzania - Frank Ching'ali; Goodluck Jacob; Edgar Nderego (IRASS Journal of Arts Humanities and Social Sciences, 2026)
This study examined the relationship between school-based incentives and teachers’ commitment to classroom instruction in public secondary schools in Kwimba District, Tanzania. A quantitative approach and cross-sectional survey design were employed. The target population comprised 888 teachers, of whom 88 teachers were selected using simple random samplings. Data was collected through a questionnaire and analyzed using SPSS version 27. Descriptive statistics and simple linear regression were used to analyze the data. The findings showed that recognition awards/certificates (M = 4.01), incentives for improving instruction (M = 3.95), and monetary incentives (M = 3.82) were highly rated, while leadership feedback, fair distribution, and timely incentive payments received relatively lower ratings. Teachers also demonstrated high commitment, particularly in willingness to put in extra effort (M = 4.15), sense of belonging (M = 4.08), and motivation for student success (M = 4.05). Regression results revealed a moderate positive relationship between school-based incentives and teachers’ commitment (R = 0.632), with incentives explaining 39.9% of the variation in commitment (R² = 0.399). The regression model was statistically significant, F (1,238) = 158.43, p < 0.001, while school-based incentives significantly predicted teachers’ commitment (B = 0.587, β = 0.632, t = 12.59, p < 0.001). The study concludes that well-designed school-based incentives significantly contribute to teachers’ commitment to classroom instruction. It recommends strengthening fair, transparent, timely, and diverse incentive systems alongside supportive leadership, professional development, and conducive working conditions.